2021
DOI: 10.3390/f12101315
|View full text |Cite
|
Sign up to set email alerts
|

Populus euphratica Phenology and Its Response to Climate Change in the Upper Tarim River Basin, NW China

Abstract: Quantifying the phenological variations of Populus euphratica Olivier (P. euphratica) resulting from climate change is vital for desert ecosystems. There has previously been great progress in the influence of climate change on vegetation phenology, but knowledge of the variations in P. euphratica phenology is lacking in extremely arid areas. In this study, a modified method was proposed to explore P. euphratica phenology and its response to climate change using 18-year Global Land Surface Satellite (GLASS) lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Several studies have been undertaken in this area in the last few years, showing that tree-ring records can broadly reflect ecological and environmental change information such as runoff [21], groundwater [22,23], water supply response [24][25][26], water use efficiency [27], and P. euphratica status [28]. The impact of ecological water transfer projects is weaker at the upstream end of the Tarim River Basin than at the downstream end of the Tarim River Basin [29]. P. euphratica growth relies mainly on groundwater, and tree-ring width is not sensitive to temperature and precipitation, so alternative tree-ring parameters need to be considered for past climate change studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been undertaken in this area in the last few years, showing that tree-ring records can broadly reflect ecological and environmental change information such as runoff [21], groundwater [22,23], water supply response [24][25][26], water use efficiency [27], and P. euphratica status [28]. The impact of ecological water transfer projects is weaker at the upstream end of the Tarim River Basin than at the downstream end of the Tarim River Basin [29]. P. euphratica growth relies mainly on groundwater, and tree-ring width is not sensitive to temperature and precipitation, so alternative tree-ring parameters need to be considered for past climate change studies.…”
Section: Introductionmentioning
confidence: 99%
“…The phenology of Populus euphratica and its response to climate change were studied. Finally, it was found that runoff was the more critical factor to control the phenology of Populus euphratica in this area [34]. Huang et al based on MODIS NDVI time series data, using wavelet transform and discriminant analysis method, evaluated the damage degree of Apocheima cinerarius to the health of Populus euphratica forest.…”
Section: Introductionmentioning
confidence: 99%